Copper-catalyzed oxidative dehydrogenative dearomatization of indole derivatives: A new strategy to construct spirocyclic indolenines - Junli Chao; Yuanyuan Yue; Ke Wang; Xiaohui Guo; Chunying Sun; Yue Xu; Jianming Liu (iScience, 2022)
Summary: A concise copper-catalyzed oxidative dehydrogenative dearomatization of indole derivatives for the direct synthesis of spirocyclic indolenines containing fluorene and indeno[2,1-b]indole groups has been established. The utility of this method has also been successfully accomplished by dual oxidative dehydrogenative dearomatization to deliver the desired spirocyclic indolenines containing fluorene groups. According to mechanistic analyses, the C-H cleavage of the phenyl ring was not implicated in the rate-limiting phase. This transformation underwent a single-electron-transfer oxidation by copper(II) catalyst to afford a radical-cation intermediate, yielding the final product by nucleophilic attack and dual deprotonation.